Pengetahuan Ibu Hamil Primigravida Tentang Persiapan Persalinan Di Desa Wonorejo Kecamatan Mojolaban Kabupaten Sukoharjo - Ana Yuliana; Tri Wahyuni (Universitas Duta Bangsa Surakarta, 2020)
Background: Maternal unpreparedness in facing childbirth is one of the factors causing the high MMR,which is 306 per 100,000 live births in 2019. 90% of maternal mortality occurred around delivery and 95%of the causes of death were obstetric complications that were often not predicted beforehand. At the time ofdelivery, if obstetric complications are found and the mother does not understand the preparations neededfor delivery, the mother does not get appropriate and timely services, resulting in three delays in referrals.This study aims to describe the knowledge of primigravida pregnant women about preparation for childbirthin Wonorejo Village, Mojolaban District, Sukoharjo Regency.Methods: This type of research is quantitative descriptive, the research location is in Wonorejo Village,Mojolaban District, Sukoharjo Regency, the total sample is 30 people, with the sampling technique usingsaturated sampling. The data collection tool used was a questionnaire. The data analysis used was univariateanalysis.Results: The knowledge of primigravida pregnant women about preparation for delivery was in the moderatecategory as many as 21 respondents (70%).Conclusion: Most of the primigravida pregnant women had sufficient knowledge, namely 21 respondents(70%).